The Victoria History of the County of Oxford: Volume XX. The South Oxfordshire Chilterns: Cavesham, Goring and Area - Keats-Rohan, Katharine (Medieval Settlement Research, 2023)
The Victoria County History project was founded in 1899 as a national project to write the history of every English county. Its stated aims are, according to the website of its host the Institute of Historical Research in London, to produce ‘authoritative, encyclopaedic histories of each county, from the earliest archaeological records to the present day, as well as topics such as topography, landscape and the built environment’. Over the course of more than a century, the iconic red volumes have continued to appear. The series was re-dedicated in 2012 to Elizabeth II, whose death was announced late on 8 September 2022, only hours after the publication of the most recent red book, the two-part volume XX of the Essex County History, was tweeted by the IHR team. Though with many volumes still to be completed, the series is an established national treasure, the starting-point for any local history research and a much-used vade mecum thereafter.